The genes coding for the muscle contractile proteins, myosin heavy chain, myosin light chain 2, and skeletal muscle actin are located on three different mouse chromosomes. - Czosnek, H (1982)
The chromosomal distribution of murine genes expressed during differentiation of skeletal muscle cells was determined by Southern blot analysis of DNA from mouse-Chinese hamster hybrid cell lines containing incomplete subsets of mouse chromosomes. All detectable myosin heavy chain genes are located on chromosome 11. The gene for the myosin light chain 2 is located on chromosome 7. The skeletal muscle alpha-actin gene and several other actin genes, or pseudogenes, are located on chromosome 3. Additional actin DNA sequences are distributed on other mouse chromosomes.